Molecular Epidemiology of Group A Streptococcus Infections in The Gambia - Sona Jabang; Annette Erhart; Saffiatou Darboe; Aru-Kumba Baldeh; Valerie Delforge; Gabriella Watson; Ebenezer Foster-Nyarko; Rasheed Salaudeen; Bolarinde Lawal; Grant Mackenzie; Anne Botteaux; Martin Antonio; et al. (Vaccines, 2021)
Molecular epidemiological data on Group A Streptococcus (GAS) infection in Africa is scarce. We characterized the emm-types and emm-clusters of 433 stored clinical GAS isolates from The Gambia collected between 2004 and 2018. To reduce the potential for strain mistyping, we used a newly published primer for emm-typing. There was considerable strain diversity, highlighting the need for vaccine development offering broad strain protection.